Changes in forest structure along a chronosequence in the black spruce boreal forest: Identifying structures to be reproduced through silvicultural practices. (February 2019) - Moussaoui, Louiza; Leduc, Alain; Fenton, Nicole J.; Lafleur, Benoit; Bergeron, Yves
Highlights: Forest stand structure in black spruce forests is varied. Changes in forest structure are controlled by the time since last fire. Changes in forest structure along a chronosequence vary with surficial deposit type. A key for field identification of forest diameter structure is proposed. Abstract: In managed boreal forests, partial harvesting has been proposed to promote forest structural complexity and to therefore maintain associated biodiversity. However, there have been few studies identifying forest structures that should be maintained within the forest matrix, and fewer still on changes in these structures during succession. Consequently, there is no tool to identify these different structures in the field or their sequence along natural succession. This study proposes a key that can be used in the field and allows for the identification of different forest diameter structures along a successional sequence in the black spruce boreal forest. The specific objectives of this study were (1) to classify the types of forest structures encountered in natural black spruce boreal forest based on their diameter distribution, and (2) to link this classification to time since last fire and its spatial homogeneity at the stand level. This study shows that the forest stand structure, in black spruce forests, is varied and that this structural variety is mainly controlled by time since last fire. It also shows that the timing of stand structural maturation varies with severity of the last fire and surficial deposit. The identification key suggests that based on tree diameter distribution it is possible to discriminate among young, mature and old forest structures, which could help forest managers select stands to be harvested according to different objectives and hence maintain the variety of black spruce forest structures at the landscape scale.